Puzzle storage chair: Multifunction furniture / Alias Omar, Norashikin Kamarudin and Nur Aza Farahin Amirruddin - Omar, Alias; Kamarudin, Norashikin; Amirruddin, Nur Aza Farahin (2015)
This study is focusing on Puzzle Storage Chair. The main material of this furniture is blockboard. Blockboard is a wood based panel that is light in weight. Blockboard makes the product easy to move and handle. It is also easy to nail and screw during manufacturing. Puzzle Storage Chair has three functions. The functions of this furniture are mainly for seat, table and bookcase. The concept of this furniture called puzzle, because of the arrangement of furniture parts. This furniture can be turn to computer table by pulling the seat upward and push the bookcase forward. Puzzle Storage Chair is made for limited spaces for living room. Based on survey, data on 100 respondents, about 92% of them agreed with the design of Puzzle Storage Chair.